Making the most of Norwegian Schools - Boarini, Romina (OECD Publishing, 2009)
Traditionally, the Norwegian compulsory education system has focused strongly on the linked goals of equal opportunities to learn, comprehensive and inclusive education. While some of these objectives have been met successfully, a number of educational outcomes, notably measures of pupil performance at the end of compulsory schooling, are unsatisfactory. Given the significant resources devoted to education, Norway's modest performance on certain measures suggests that resources are used inefficiently. There are many possible routes to improve efficiency. This paper focuses on teaching quality, school autonomy, accountability and the level and composition of spending. Consistent policy actions should be taken in these areas, taking into account the multi-level structure of governance of the Norwegian education system
Keywords: Economics; Norway